Pengaruh Terpaan Media dan Kualitas Informasi Akun Instagram @Bogoreatery terhadap Minat Followers Berwisata Kuliner - Robiyatul Adawiyah; Yeni Nuraeni (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to analyze the influence of media exposure and information quality of the Instagram account @bogoreatery on followers' interest in culinary tourism. In today's digital era, social media such as Instagram plays an important role as a source of information and in shaping people's interests and preferences, especially in the context of culinary tourism. Media exposure and information quality are important factors that can influence a person's interest. This study will examine the Instagram account @bogoreatery by making Instagram followers @bogoreatery as the subjects in this study. This study uses a quantitative approach and the theory used as the basis for this study is the Media Richness Theory. The sampling technique used is purposive sampling with a total of 400 respondents calculated using the Slovin formula. The results of the study indicate that there is an influence between media exposure and the quality of information on the Instagram account @bogoeatery on the interest of followers in culinary tourism with an influence of 48.8%, while the rest is influenced by other factors outside the variables studied.